FAKTOR-FAKTOR PENYEBAB KURANGNYA PEMANFAATAN MEDIA BERBASIS CANVA DI TK GMIT SYALOOM - Bhoko, Fitrananda Yua; Sartika Kale; Gokma Nafita Tampubolon; Credo G. Betty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the factors contributing to the underutilization of Canva-based media. It employs a qualitative descriptive approach, with data collected through interviews involving three early childhood education teachers at TK GMIT Syaloom. Data analysis involved reduction, presentation, and conclusion drawing, while data validity was verified through source triangulation. The results indicate that the primary factors are the teachers' knowledge and skills; teachers struggle to use more complex features, preventing optimal development of learning media. Additionally, a lack of routine and sustained training has hindered the continued development of Canva usage, causing some aspects of the tool to fall into disuse.